Measuring phonons in protein crystals - Acbas, G.; Niessen, K. A.; George, D. K.; Snell, E.; Markelz, A. G. (Ultrafast Phenomena and Nanophotonics Xvii, 2013)
Using Terahertz near field microscopy we find orientation dependent narrow band absorption features for lysozyme crystals. Here we discuss identification of protein collective modes associated with the observed features. Using normal mode calculations we find good agreement with several of the measured features, suggesting that the modes arise from internal molecular motions and not crystal phonons. Such internal modes have been associated with protein function.
Keywords: correlated motions; dynamics; mode; molecular crystals; molecular vibrations; normal modes; phonons; protein dynamics; spectroscopy; Terahertz